Ionization‐Facilitated Formation of 2D (Alumino)Silicate–Noble Gas Clathrate Compounds. (6th March 2019) - Zhong, Jian‐Qiang; Wang, Mengen; Akter, Nusnin; Kestell, John D.; Niu, Tianchao; Boscoboinik, Alejandro M.; Kim, Taejin; Stacchiola, Dario J.; Wu, Qin; Lu, Deyu; Boscoboinik, Jorge Anibal
Abstract: The nanoscale confinement of noble gases at noncryogenic temperatures is crucial for many applications including noble gas separations, nuclear waste remediation, and the removal of radon. However, this process is extremely difficult primarily due to the weak trapping forces of the host matrices upon noble gas physisorption. Herein, the formation of 2D clathrate compounds, which result from trapping noble gas atoms (Ar, Kr, and Xe) inside nanocages of ultrathin silica and aluminosilicate crystalline nanoporous frameworks at 300 K, is reported. The formation of the 2D clathrate compounds is attributed to a novel activated physisorption mechanism, facilitated by ionization of noble gas atoms. Combined X‐ray photoelectron spectroscopy (XPS) and density functional theory (DFT) studies provide evidence of an initial ionization process that significantly reduces the apparent trapping barrier. Noble gas ions become neutralized upon entering the cages, and their desorption requires unprecedentedly high temperatures, even in ultrahigh vacuum conditions. From 2D aluminosilicate films these temperatures are 348 K (Ar), 498 K (Kr), and 673 K (Xe). DFT calculations also predict that Rn can be trapped in 2D aluminosilicates with an even higher desorption temperature of 775 K. This work highlights a new ionization‐facilitated trapping mechanism resulting in the thinnest family of clathrates ever reported. Abstract : 2D noble gas–(alumino)silicate clathrates are formed via a novel activated physisorption mechanism at room temperature. They are formed by trapping single noble gas atoms (Ar, Kr, and Xe) inside nanocages of 0.5 nm thick crystalline nanoporous frameworks. These are the thinnest clathrates ever reported and they show high thermal stability: 348 K (Ar), 498 K (Kr), and 673 K (Xe).